Welding Residual Stress Distribution of U-Rib Stiffened Plates of Steel Box Girders and its Influence on Structural Natural Frequencies - Chen, Li; Wang, Tianqi; Pan, Jianrong; Ma, Niujing; Wang, Ronghui (Frontiers in Materials, 2022)
This paper mainly explores the distribution of welding residual stress of U-rib stiffened plates of steel box girders and examines the influence of welding residual stress over the natural frequencies of these plates. The research focuses on two aspects, namely, the distribution of welding residual stress, and the dynamic behavior of U-rib stiffened plates in the context of that distribution. Firstly, we build two finite element models to analyses the welding process and study the dynamic behavior. Next, the authors discussed how different geometric parameters, as well as welding parameters, affect the residual stress distribution. In addition, the welding residual stress curves were fitted for steel box girders of varied sizes, and a simplified formula was deduced for the distribution of welding residual stress. After that, the simplified formula was applied to analyze the natural frequencies of stiffened plates in multiple sets of models. Through the analysis of natural frequency under different boundary conditions, it was learned that the welding residual stress has a remarkable influence on the natural frequencies of stiffened plates.